Assessing rainfall trends and variability in a climate change / Muhammad Fahmi Muhammad Iskandar … [et al] - Muhammad Iskandar, Muhammad Fahmi; Ibrahim, Anas; Mohtar, Zul Azmi; Pakir Mohamed Latif, Muhammad Faizal; E.M Yahaya, Nasehir Khan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Southeast Asia, home to a population of 691.97 million people, faces significant challenges related to rainfall patterns. This study critically reviews 40 articles to explore the intricate rainfall patterns across 11 Southeast Asian countries, examining seasonal variations, impacts, influencing factors, and mitigation strategies. The objective is to develop a comprehensive understanding of rainfall dynamics in the region, particularly its influence on the region’s ecosystem and livelihoods. The analysis reveals distinct seasonal periods, with June to September marking the peak rainfall period due to the summer monsoon season, while November to April signifies the onset of dry seasons in several countries. Rainfall impact range plays a crucial role in the economies of nations, particularly in the agricultural sector, where it serves as a vital source of sustenance. However, it also poses risks, including flooding, landslides, and drought. The study emphasizes the significant role of the El Niño Southern Oscillation (ENSO) in influencing rainfall variability across Southeast Asia, with El Niño events often associated with drier conditions and La Niña events with wetter conditions. To mitigate these challenges, Southeast Asian nations have implemented various strategies, including infrastructure development, community-based initiatives, and awareness campaigns. Further research is needed to explore specific factors influencing rainfall in each country, develop more accurate forecasting models, investigate innovative mitigation strategies, and evaluate the effectiveness of existing measures.